Peran Kitchen Management dalam Penerapan FIFO pada Operasional Dapur di Hotel Padma Resort Legian - I Nyoman Arta Ribawa Gunawan; Pondang Polikarpus Nainggolan; I Made Agung Rai Antara (Ekodestinasi, 2026)
This study aims to identify the obstacles in implementing the FIFO (First In First Out) system and to analyze the role of kitchen management in supervising and controlling its implementation in kitchen operations at Padma Resort Legian. The research employed a descriptive qualitative method with data collection techniques including observation, interviews, and documentation. The informants consisted of 8 individuals: Executive Chef, Executive Sous Chef, Junior Sous Chef, Chef de Partie, and Commis. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results indicate that FIFO implementation has been carried out according to standard operating procedures through proper storage arrangement, labeling, and inventory recording, but it is not yet optimal. The main obstacles include high operational workload, limited storage space, lack of staff consistency, inadequate labeling, and insufficient supervision. Kitchen management plays a crucial role in ensuring effective FIFO implementation through SOP planning, direct supervision, inventory control systems, and staff training. Therefore, improved supervision, coordination, and continuous training are necessary to optimize FIFO implementation.